Key to chironomid pupal exuviae (Diptera: Chironomidae) of tropical high Andean streams - Prat, Narcís (2014)
The Chironomidae is a cosmopolitan family of Nematoceran flies with more than 20 000 species described. However the diversity of genera and species of the family in the Andean region beyond the 2 000m.a.s.l are scarcely known. We conducted faunal surveys and biomonitoring research in different streams of Colombia, Ecuador and Peru from May 2005 to October 2011. Based on specimens collections, and a taxonomic key was developed to identify pupae and pupal exuviae of 46 genera of midges (Diptera, Chironomidae) collected from streams at high altitude areas on the Andean tropical mountains. We included illustrations and brief taxonomic descriptions for all genera, of which several ones have not yet been formally described; in this latter case we used the nomenclature of Roback & Coffman (1983). For two genera, Cricotopus and Genus 1, keys to the most common morphospecies were provided. Results showed that in this area the chironomid assemblages are dominated by the members of the subfamily Orthocladiinae (22 genera) followed by the Chironominae (13). Six genera of Tanypodinae were identified, while only three and two genera were present from subfamilies Podonominae and Diamesinae. This key may be very useful for both studies about drift in streams, and for biomonitoring purposes.